Lactobacillus paracasei WIS43 alleviates DSS-induced colitis by modulating gut microbiota and suppressing inflammation - Fu, Yu; Chen, Shuxia; Cui, Lei; Cao, Ying; Dong, Yanan; Duan, Yunfeng; Wu, Chongming (Frontiers in Microbiology, 2026)
IntroductionUlcerative colitis (UC) is a chronic inflammatory disorder of the colon with rising incidence and limited therapeutic options. Probiotics are increasingly recognized as potential interventions, but strain-specific differences remain insufficiently defined.MethodsWe conducted a meta-analysis of publicly available microbiome datasets to characterize disease-associated dysbiosis, focusing on the genus Lactobacillus. We then evaluated Lactobacillus paracasei WIS43, a novel strain isolated from the breast milk of a healthy volunteer, in a dextran sulfate sodium (DSS)-induced murine colitis model, using mesalazine and the commercial strain Lactobacillus paracasei LPC-37 as comparators. Disease severity, histopathology, inflammatory cytokines, and gut microbiota composition were systematically assessed.ResultsMeta-analysis confirmed a significant depletion of Lactobacillus in UC patients. In vivo, WIS43 treatment reduced body weight loss, disease activity index scores, and colon shortening. Histological analysis revealed preserved epithelial integrity and reduced inflammatory infiltration. WIS43 significantly decreased serum and colonic TNF-α, IL-6, and IL-1β levels, demonstrating stronger anti-inflammatory activity than LPC-37 and comparable efficacy to mesalazine. 16S rRNA sequencing further showed that WIS43 restored beneficial taxa, including Lactobacillus johnsonii and Lactobacillus taiwanensis, while reducing potentially pathogenic bacteria.ConclusionThese findings identify WIS43 as a promising probiotic candidate for the prevention and treatment of UC, supporting its therapeutic potential through coordinated modulation of host immunity and gut microbiota.